Integrating phylogeography and species distribution models: cryptic distributional responses to past climate change in an endemic rodent from the central Chile hotspot. Issue 6 (23rd March 2016) - Gutiérrez‐Tapia, Pablo; Palma, R. Eduardo
Abstract: Aim: Biodiversity losses under the species level may have been severely underestimated in future global climate change scenarios. Therefore, it is important to characterize the diversity units at this level, as well as to understand their ecological responses to climatic forcings. We have chosen an endemic rodent from a highly endangered ecogeographic area as a model to look for distributional responses below the species level: Phyllotis darwini . Location: The central Chile biodiversity hotspot: This area harbours a high number of endemic species, and it is known to have experienced vegetational displacements between two mountain systems during and after the Last Glacial Maximum. Methods: We have characterized cryptic lineages inside P. darwini in a classic phylogeographic approach; those intraspecific lineages were considered as relevant units to construct distribution models at Last Glacial Maximum and at present, as border climatic conditions. Differences in distribution between border conditions for each lineage were interpreted as distributional responses to post‐glacial climate change. Results: The species is composed of two major phylogroups: one of them has a broad distribution not only across the valley but also in mountain ranges, whereas the other displays a disjunct distribution across both mountain ranges and always above 1500 m. The lineage distribution model under LGM climatic conditions suggests that both lineages were codistributed in the southern portion of P. darwini's current geographic range, mainly at the valley and at the coast. Main conclusions: Present distribution of lineages in P. darwini is the consequence of a cryptic distributional response to climate change after LGM: post‐glacial northward colonization, with strict altitudinal segregation of both phylogroups.